Perputaran Piutang Pada Pasien BPJS di Rumah Sakit AB Gresik Tahun 2022 - Yunita Dewi Nurjanah; Wasti Reviandani (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2024)
The turnover of patient receivables from BPJS at AB Hospital in 2022 was the subject of a qualitative descriptive study. Through interviews and observations, AB Hospital was found to be very good at managing receivables. However, calculations based on AB Hospital's criteria indicated that the Receivable Turnover for the year 2020 could be categorized as low. According to AB Hospital's financial standards, the Average Collection Period (ACP) for current receivables is considered quite good as it meets the hospital's requirements, whereas the ACP for non-current receivables is considered low.